Midazolam premedication for Ketamine-induced emergence phenomenon: A prospective observational study - Deepa Kameswari Perumal; Mangaiarkkarasi Adhimoolam; Nitya Selvaraj; Suneeth Pullikotil Lazarus; Meher Ali Raja Mohammed (Wolters Kluwer Medknow Publications, 2015)
Objective: Ketamine administration is known to induce hemodynamic pressor response and psychomimetic effects which could be attenuated by appropriate premedication. The present study was designed to evaluate the effect of midazolam on hemodynamic stability and postoperative emergence phenomenon following ketamine anesthesia. Methods: This was a prospective observational study including 30 adult patients with American Society of Anesthesiologists physical grades I and II scheduled for elective short surgeries under ketamine anesthesia. Patients were premedicated with midazolam (0.02 mg/kg intravenously) before the ketamine induction (1 mg/kg intravenously). Demographic data and hemodynamic variables were observed during the perioperative period. Pain score by visual analog scale score and psychomimetic effects were recorded postoperatively. Findings: The mean ± standard deviation of heart rate, systolic blood pressure, diastolic blood pressure, and respiratory rate were decreased postoperatively (85.3 ± 11.4, 120.7 ± 8.2, 79.2 ± 5.5, 13.5 ± 1.8, respectively) compared to intraoperative period (88.53 ± 14.1, 123.83 ± 13.8, 83 ± 9.1, 14.13 ± 2.0, respectively). There was statistically significant decrease in systolic (P = 0.03) and diastolic (P = 0.002) blood pressure, but not with heart rate and respiratory rate. Eighty percent of patients had no pain at ½ hour and 1 hour, while this increased to 90% at 2 hours postoperatively. Mild emergence delirium was noted in 13.3% and 16.7% at ½ hour and 1 hour, respectively, which decreased to 13.3% at 2 hours. Dreams were noticed in 20%, 27% and 10% of patients at ½ hour, 1 and 2 hours after surgery, respectively. Conclusion: Midazolam premedication in ketamine anesthesia effectively attenuated the hemodynamic pressor response and postoperative emergence phenomenon. Hence, the combination of midazolam with ketamine can be safely used for short surgical painful procedures in adults.